"We Must All Be Ready for Major Changes": Visiting Climate for Change at the Norwegian Petroleum Museum. Issue 1 (1st March 2022) - Ruud, Lise Camilla; Thorstensen, Erik
Abstract: This article analyzes a current exhibition, Climate for Change, which opened at the Norwegian Petroleum Museum in 2019. By engaging with the way in which the exhibition constructs a "we, " the article proceeds to examine how agency for mitigation is presented and analyzed. It assesses how futures are created and what types of futures emerge. These themes are addressed with reference to insights from museum research and energy humanities. The choices in the exhibition point toward a traditional understanding of continuities, of agency, and of future visions while tending toward a reduction of Norwegian accountability for climate change.